The Relationships between Mass Media Exposure and Family Environment with Health Reproduction Among Girls of XI Class in SMA Negeri 10 Bengkulu - Sanisahhuri Sanisahhuri; Buyung Keraman; Deta Oktariana (Jurnal Sains Kesehatan, 2018)
One effort to improve the quality of human life can be done through efforts to improve health including reproductive health. This study aimed to study                      the relationship between mass media exposure and family environment with reproductive health in girls of class XI in SMA Negeri 10 Kota Bengkulu. The type of research was Analytic Survey. The study design was Cross Sectional. The sample of the research was all girls of class XI in SMA Negeri 10 Kota Bengkulu which amounts to 87 girls. Sampling technique used is Total Sampling. Data collection techniques used primary and secondary data. Data analysis used univariate and bivariate analysis. Bivariate analysis using Chi-Square test.                   To know the closeness of the relationship was used statistical test Contingency Coefficient (C). The results of  the study showed that of 87 girls, 71 girls (81.6%) got information from the family environment, 76 girls (87.4%) were exposed to mass media, 73 girls (83.9%) had health healthy reproduction, there was no significant relationship between mass media exposure and reproductive health of girls, and there was a significant relationship between the family environment with reproductive health of  girls with weak relationship categories. It was suggested to the school to be able to conduct counseling and seminar related to reproductive health for young women. Keywords: family environment, mass media, reproductive health